A 2E, energy and environment performance of an optimized vernacular house for passive cooling - Case of North-East India. (1st February 2023) - Gupta, Sudhir Kumar; Chanda, Prayag Raj; Biswas, Agnimitra
Abstract: Energy consumption in buildings has been increasing in recent years due to global warming, resulting in the increased use of HVACs, and causing environmental pollution. To fulfill the target of net-zero energy building and less building-generated pollution, vernacular houses can be constructed for their climate-adaptive architectural design, natural ventilation, and low cost. However, such houses suffer from excessive heat gain in summer due to large window openings, infiltration, and occupancy. There is also a lack of understanding of the energy and environment (2E) performance of a vernacular house in passive cooling compared to modern buildings with active cooling features. This paper aims to find optimal energy-efficient and environment-friendly passive cooling features that can be integrated with a 1BHK vernacular house for summer cooling as a case for North-East India. This study employs a simulation-based multi-objective optimization method that combines the architectural modeling tool EnergyPlus with a non-sorting genetic algorithm (NSGA-II) to find the best possible combinations of different passive cooling features. The findings show that conventional vernacular houses can be more energy efficient and eco-friendly by incorporating passive cooling strategies. The most optimal design is obtained with passive cooling elements, such as an external wall bonded with paraffin, cemented ground floor, false roof, double blue 6 mm air glazing, 1.5 m overhang, and the window-to-wall ratio of 32%, and site orientation of 167°. The optimal passive house has resulted in nearly 50.45% of energy savings and 29.40% less operational and embodied carbon emissions than conventional buildings. Thus, this study contributes to the debate over the applicability of different passive cooling strategies in vernacular houses and encourages further exploration. Highlights: One BHK vernacular house modeled in DesignBuilder for hot and humid summer. Optimal selection of passive cooling features for vernacular house done. Validated model of DesignBuilder used for optimal selection of passive cooling features. NSGA-II optimization performed involving 2Es for the vernacular house. Savings in Cooling load and reduction in CO2 achieved with the optimal design.